1145 RTMS TREATMENT IMPROVED COGNITIVE DYSFUNCTION THROUGH ADULT NEUROGENESIS IN ICV-STZ RAT MODEL OF SPORADIC ALZHEIMER'S DISEASE. (16th January 2023) - Roy, A; Kumar, A; Kakkadi, V; Nag, T C; Katyal, J; Gupta, Y K; Jain, S
Abstract: Background: Intracerebroventricular streptozotocin injection at 3mg/kg of b/w causes phenotypes similar to that of sporadic Alzheimer's disease (sAD) from 14th day post-injection. On the other hand, the body of evidence indicated that impairment in the sAD is the major contributor for cognitive decline. Taken together, we tested the adult neurogenesis hypothesis in streptozotocin model of sAD in female Wistar rats after extremely low magnetic stimulation (MF: 17.96, 50Hz, 2hr/day, 21days). Method: 33 rats were randomly divided into three groups viz. Sham+MF, AD and AD+MF. Consequently, animals were first induced AD with stereotaxic manipulation and then they were exposed to low frequency magnetic field stimulation, followed by terminal cognitive behavioural tasks brain tissue being isolated for both biochemical and subcellular expression experiments (ethical no. 12/IAEC-1/2017) . Results: Showed reduction in latency to the goal quadrant (p= 0.002) and transfer latency (p= 0.045) in AD+MF group versus AD. Even, Dirichlet distribution of time spent in 4 quadrants indicated un-uniform in all the groups except AD group (p= 0.067, LRS= 7.35). Further, cell count in CA3 and DG exhibited increase in cell density in AD+MF group (p<0.05). However, we found significant reduction in SOD1 activity after MF treatment (p= 0.035) but no change in GSH level in hippocampus and frontal cortex. Interestingly, these changes in AD+MF animals are associated with increase in density of BrdU+/Nestin+ cells in granular layer (p= 0.002) and hilus region (p= 0.0005) of DG along with increase in expression of L-type Ca2+ channels as compared to AD group. Conclusion: This experimental evidence suggests that non-invasive brain stimulation can promote adult neurogenesis by activating L-type ca2+ channels in the hilus, which intern helps in retention of long-term memory even after sAD.